IMPLEMENTATION OF VILLAGE FUND MANAGEMENT IN INFRASTRUCTURE DEVELOPMENT IN BELERANG VILLAGE - Bayu, Krisna; Hatta, Sukarno; Bahar, Asriyanti; Tsurayyah , Adilah (Jurnal Ilmiah Administrasita', 2024)
This study aims to determine the implementation of village fund management in infrastructure development in Belerang Village, Sinjai Borong District, Sinjai Regency. In this study the authors used qualitative research methods with literature review data collection techniques. Based on the results of the study, the implementation of village fund management by the Batu Belerang Village Government can be said to be appropriate, in the implementation of village fund program activities carried out by involving the community in the process of activities The village government invites the community in the process of village fund activities, for example, such as when building concrete roads on village roads, making rice field drains, and also making farm roads. The cooperation carried out by the Batu Belerang Village government and the Batu Belerang Village community is very good, this can occur because of the awareness of the community about the importance of the village fund program for themselves, assisted again by counseling activities to the community about the village fund program so that the Batu Belerang Village community feels that the Village Fund is the responsibility of the village government and the Batu Belerang Village community.